A PRELIMINARY STUDY OF LOW-CODE/NO-CODE ECOSYSTEM PRACTICES: TRANSLATING DESIGN STUDENT VIEWS ON CRAFTING INTERACTIVE DESIGN - Azwan, Abidin; Noorhaslina, Senin; Ahmad Azaini, Abdul Manaf (Aliva Global Research and Development, 2021)
The low-code/no-code (LCNC) ecosystem practices for interactive design platforms has started to emerged to alleviate the processes of digital transformation by enabling individuals with nonprogramming experience to participate in crafting digital products. Indirectly, the waves of this ecosystem affect learning environments in design education and act as a catalyst for translating design ideas into front-end logical code without coding. This article highlights the insights of design students' experiences from LCNC practices during an interactive design course at UNIMAS, Malaysia. This study used a qualitative research approach strategy of an online survey. This study has shed light on the important need for a new paradigm in teaching-learning activities in design education, as evidenced by the advancement of LCNC practices that can be embedded in related design courses. It was discovered that minimizing the time required to synthesize UX design to completion and reducing the complexity of the design process within a given timeframe, are the two most critical views of LCNC practices in the learning process for interactive design. In conclusion, by understanding the LCNC ecosystem for design education, this approach offers a window into an alternative method for practical interactive design learning and can assist students in breaking the programming barrier, as LCNC platforms continue to grow in trend steadily